Gender and mobile payment system adoption among students of tertiary institutions in Nigeria - Hamza, Aminu; Shah, Asadullah (International Journal of Computer and I nformation Technology, 2014)
This study examines the relationship between gender and the factors that determine the adoption of mobile payment system among the students of tertiary institutions in Nigeria. The researchers focused especially on examining how the influence of the predicting variables differs by gender of the users.Technology Acceptance Model (TAM) was used with two additional variables to form the conceptual model which comprises of perceived usefulness 9PU) perceived ease of use (PEOU) perceived compatibility (PC) and social norm (SN. Survey research method was used which involved the students of Bayero University of Science Kano 9BUK), North-West University, and Kano university of Science and Technology (KUST) Wudil, Kano, Nigeria. Of the 400 questionnaire distributed, 214 valid questionnaire were used. Our findings reveal that PEOU, PU and SN influence the behavioral intention to adapt mobile payment system among the students. The findings from the independent t-test also revealed that the influence of PEOU and SN differs among the gender of the students, with male students having higher perceived ease use (PEOU) over their female counterpart, while social norm (SN) influence female students more than their counterpart in adopting mobile payment. However, no significant difference was found in the general adoption of the mobile payment system among gender. The implications for both practitioners and academia as well as recommendations for future studies were also discussed